Mission to 'Those of Riper Years'. (July 2020) - Woolnough, Brian E
This paper argues that the church should give especial care to the needs of older folk in their communities, needs that are often neglected. It analyses why such folk have especial needs in our contemporary society and suggests practical ways that churches can and should respond. It summarises particular approaches to learning to grow old, and to die well, given by various authors who have had experience in these areas. It considers the problem of pain and suffering and suggests a dualistic approach that can give comfort.